Antimycobacterial and photosynthetic electron transport inhibiting activity of ring-substituted 4-arylamino-7-chloroquinolinium chlorides - Otevrel, Jan; Bobal, Pavel; Zadrazilova, Iveta; Govender, Rodney; Pesko, Matus; Keltosova, Stanislava; Koleckarova, Petra; Marsalek, Petr; Imramovsky, Ales; Coffey, Aidan; O'Mahony, Jim; Kollar, Peter; et al. (Molecules (Basel, Switzerland), 2013)
In this study, a series of twenty-five ring-substituted 4-arylamino-7-chloroquinolinium chlorides were prepared and characterized. The compounds were tested for their activity related to inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts and also primary in vitro screening of the synthesized compounds was performed against mycobacterial species. 4-[(2-Bromophenyl)amino]-7-chloroquinolinium chloride showed high biological activity against M. marinum, M. kansasii, M. smegmatis and 7-chloro-4-[(2-methylphenyl)amino]quinolinium chloride demonstrated noteworthy biological activity against M. smegmatis and M. avium subsp. paratuberculosis. The most effective compounds demonstrated quite low toxicity (LD₅₀ > 20 μmol/L) against the human monocytic leukemia THP-1 cell line within preliminary in vitro cytotoxicity screening. The tested compounds were found to inhibit PET in photosystem II. The PET-inhibiting activity expressed by IC₅₀ value of the most active compound 7-chloro-4-[(3-trifluoromethylphenyl)amino]quinolinium chloride was 27 μmol/L and PET-inhibiting activity of ortho-substituted compounds was significantly lower than this of meta- and para-substituted ones. The structure-activity relationships are discussed for all compounds.
Keywords: transport elektronů; buněčné linie; lidé; vztahy mezi strukturou a aktivitou; chloridy; Chloroplasts; antituberkulotika; Cell Line; Photosynthesis; Drug Evaluation, Preclinical; Cell Survival; Humans; Spinacia oleracea; inhibiční koncentrace 50; preklinické hodnocení léčiv; Microbial Sensitivity Tests; Solubility; rozpustnost; mikrobiální testy citlivosti; Structure-Activity Relationship; Quinolinium Compounds; fotosyntéza; viabilita buněk; Electron Transport; Chlorides; Mycobacterium; Antitubercular Agents; chinolinové sloučeniny; chloroplasty; Inhibitory Concentration 50